Legalising prostitution in Malaysia / Jenita Kanapathy - Jenita, Kanapathy (2011)

(untitled)
Malaysian law criminalises prostitution under ·the Penal Code. In spite of this, prostitution continues to thrive in Malaysia. The aim of this project paper is to provide supportive arguments why legalising prostitution in Malaysia would be a better alternative as compared to the criminalisation approach. In this paper, prostitution is confined to commercialised sexual gratification between opposite sexes and does not include child prostitution, lesqian, gays, bisexuals and transvestites. The paper also presents arguments on how the current legislation in Malaysia deprives the sex .workers of their fundamental rights as guaranteed by the Federal Constitution and how it should be reformed in order to confer sex workers, equal legal standing just like any other legitimate profession. In addition, it also examines the legal frameworks of the sex sector adopted by different countries namely India, Singapore, Hong Ko~g and Turkey in order to develop a workable legal frame work for use in the Malaysian context. Finally, the paper delineates the challenges that would be faced to realise the proposed legal framework for Malaysia.